Proceso de ASC - ANÁLISIS DE LA PERSONALIZACIÓN POLÍTICA: UNA ESTRATEGIA DE ADAPTACIÓN DE LOS PARTIDOS EN COLOMBIA. (2020)
The personalization of politics is a phenomenon with greater implications in presidential systems. This paper studies the effect that Uribe has had on the electoral and party system in Colombia. The basis of the electoral system currently in Colombia is derived from reform of 2003. Several authors argue that this reform alludes to the intentions of Uribe and part of the political class to reform the electoral dynamics in Colombia. Key aspects of the new electoral system of 2003 introduced several elements that substantially modified the electoral system. We seek to identify the possible electoral niches favorable to Uribe as well as the main characteristics of these territories with the intention of making a diagnosis regarding the "pro-Uribe" electorates.